Intelligent quad cane with GPS allocation for Tachyarrhthmia / Norain Rahim … [et al.] - Rahim, Norain; Ab Aziz, Ab Wafi; Rosdi, Rafi’uddin; Wan Hassan, Wan Haszerila; Che Aziz, Siti Asma (Division of Research and Industry Linkages, 2017)
The aim o f this paper is to present the development of an Intelligent Quad Cane with Global Positioning System (GPS) Allocation for Tachyarrhythmia. Heart attack symptoms are vary between individual. Usually, senior citizen or cardiovascular patient is not aware of their heart beat rate. Lack of early warning is the most common reason of the patient die because of heart attack. Thus, this project offers an early warning for cardiovascular patient to the charged person. Furthermore, this project is able to analyze and indicate abnormality in heart rate pulse for the user. Sinus tachycardia and Supraventricular tachycardia was chosen as research subject because these disease is an early complication of the heart attack. The uses of Global System for Mobile (GSM) and GPS modules in this project can make the charged person receives the notification from the patient via Short Message Service (SMS) which contains the exact location together with patient's condition. This condition shortens the time of ambulance to arrive.